No evidence for asymmetric sperm deposition in a species with asymmetric male genitalia - van Gammeren, Sanne; Lang, Michael; Rücklin, Martin; Schilthuizen, Menno (PeerJ, 2022)
Background Asymmetric genitalia have repeatedly evolved in animals, yet the underlying causes for their evolution are mostly unknown. The fruit fly Drosophila pachea has asymmetric external genitalia and an asymmetric phallus with a right-sided phallotrema (opening for sperm release). The complex of female and male genitalia is asymmetrically twisted during copulation and males adopt a right-sided copulation posture on top of the female. We wished to investigate if asymmetric male genital morphology and a twisted gentitalia complex may be associated with differential allocation of sperm into female sperm storage organs. Methods We examined the internal complex of female and male reproductive organs by micro-computed tomography and synchrotron X-ray tomography before, during and after copulation. In addition, we monitored sperm aggregation states and timing of sperm transfer during copulation by premature interruption of copulation at different time-points. Results The asymmetric phallus is located at the most caudal end of the female abdomen during copulation. The female reproductive tract, in particular the oviduct, re-arranges during copulation. It is narrow in virgin females and forms a broad vesicle at 20 min after the start of copulation. Sperm transfer into female sperm storage organs (spermathecae) was only in a minority of examined copulation trials (13/64). Also, we found that sperm was mainly transferred early, at 2–4 min after the start of copulation. We did not detect a particular pattern of sperm allocation in the left or right spermathecae. Sperm adopted a granular or filamentous aggregation state in the female uterus and spermathecae, respectively. Discussion No evidence for asymmetric sperm deposition was identified that could be associated with asymmetric genital morphology or twisted complexing of genitalia. Male genital asymmetry may potentially have evolved as a consequence of a complex internal alignment of reproductive organs during copulation in order to optimize low sperm transfer rates.
Keywords: Asymmetric genitalia; Drosophila pachea; Sperm transfer; Copulatory complex; X-ray computed tomography